Editorial. Issue 8 (August 2020) - Mansfield-Devine, Steve
Abstract : The Russia report from the UK Parliament's Intelligence and Security Committee (ISC) has been the subject of much controversy – primarily because Prime Minister Boris Johnson blocked its scheduled publication, which would have been just before the last general election.